Ethnopedagogy in Serat Centhini - Windi Yusnita; Sri Harti Widyastuti; Afendy Widayat (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2026)
This study is motivated by concerns regarding the erosion of character among the younger generation, resulting from the disconnect between formal education and local wisdom in the era of globalization. To address this issue, the study aims to identify and analyze the integration of ethnopedagogical elements into the narrative of *Serat Centhini*, thereby contributing to the theoretical understanding of culture-based learning models. Employing a qualitative method with a textual analysis approach and an ethnopedagogical theoretical framework, the text is examined in depth to explore its narrative structure and character dialogues. The findings reveal that *Serat Centhini* effectively integrates moral teachings, ethics, and local knowledge, manifesting them into eight traditional educational values: family, responsibility, spirituality/religion, social consciousness, discipline, resilience, honesty, and fighting spirit. Consequently, this study underscores the importance of reconstructing traditional literary works as a medium for character education that is both relevant and contextual for the current generation.